2006
DOI: 10.1038/sj.bmt.1705381
|View full text |Cite
|
Sign up to set email alerts
|

Rapid helper T-cell recovery above 200 × 106/l at 3 months correlates to successful transplant outcomes after allogeneic stem cell transplantation

Abstract: The current study evaluates the role of quantitative measurement of peripheral lymphocyte subsets, especially CD4+ helper T-cell recovery, in predicting transplant outcomes including overall survival (OS) and non-relapse mortality (NRM) after allogeneic stem cell transplantation. A total of 69 allogeneic recipients were included with following diagnoses: acute myeloid leukemia 42, acute lymphoblastic leukemia 5, chronic myeloid leukemia 15, non-Hodgkin's lymphoma 5 and high-risk myelodysplastic syndrome 2. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 28 publications
7
104
2
Order By: Relevance
“…However, advantages in early T cell recovery appeared to be lost subsequently during the observation period and after 1 year comparable CD4 þ T cell counts were noted regardless of the source of graft or donor type. Recently published studies 3 have found a positive correlation between rapid CD4 þ lymphocyte recovery and outcome after transplantation. Our data suggest that, independent of investigated risk factors for delayed immune reconstitution during the first months, there is a comparable lymphocyte reconstitution 1 year after HSCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, advantages in early T cell recovery appeared to be lost subsequently during the observation period and after 1 year comparable CD4 þ T cell counts were noted regardless of the source of graft or donor type. Recently published studies 3 have found a positive correlation between rapid CD4 þ lymphocyte recovery and outcome after transplantation. Our data suggest that, independent of investigated risk factors for delayed immune reconstitution during the first months, there is a comparable lymphocyte reconstitution 1 year after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, published studies suggest that rapid T cell reconstitution may correlate positively with overall survival after allogeneic hematopoietic stem cell transplantation (alloHSCT). 3,4 For these reasons, restoration of the immune system following alloHSCT remains a focus of ongoing research.…”
Section: Introductionmentioning
confidence: 99%
“…4 Other studies have not demonstrated significantly improved immune reconstitution with RIC, 5,6 making this area a subject of continued debate (reviewed by Jimenez et al 7 ). While many previous studies of immune reconstitution post HSCT have focused on lymphocyte subset recovery, [8][9][10][11][12][13][14][15][16] we have previously shown that combined monocyte and lymphocyte recovery also has an impact on survival post myeloablative HSCT in acute leukemia due to a reduction in nonrelapse mortality. 17 Here, we test the hypothesis that both lymphocyte and monocyte recovery are similarly associated with survival in patients undergoing RIC allogeneic HSCT with fludarabine and melphalan.…”
Section: Introductionmentioning
confidence: 99%
“…In general, rapid T-cell recovery is associated with improved outcomes following allogeneic SCT. [8][9][10][11][12][13] Unfortunately, the majority of these allogeneic SCT studies have been with small patient numbers, typically incorporating a mixture of tumor types and conditioning regimes and resulting in varying conclusions. Thus, the identification of cellular effectors in the stem cell products has varied, including their relationships between clinical outcomes and recovery of CD3 þ , CD4 þ , CD8 þ or natural killer (NK) cells.…”
mentioning
confidence: 99%
“…These studies resulted in conflicting observations, including the finding of decreased GVHD following T-cell depletion, 4,5 as compared to positive correlations between the number of T cells within products, the rapidity of T-cell recovery 6,7 and improved clinical outcomes. 6,[8][9][10][11] Based on these results, current efforts to manipulate T-cell numbers and subsets within stem cell products have focused on the control of GVHD, immunologic recovery and clinical outcomes. The studies have also shown significant relationships between infused T-cell numbers, time to T-cell recovery and outcome parameters, including time to tumor progression, relapse-free survival and overall survival.…”
mentioning
confidence: 99%